Output-Based Aid in Project Finance : Using World Bank Guarantees to Enhance Credit - von Klaudy, Stephan; Goswami, Umang (World Bank, Washington, DC, 2012)
To obtain market financing for an infrastructure project, a private operator needs to be able to provide potential investors assurance that revenue flows to the project will be reliable. Where those revenue flows consist in part of government output-based aid (OBA) subsidy payments, providing that assurance can be problematic. Many governments are considered unreliable payers and therefore assigned a low credit rating by financial markets and investors. In these cases the credit quality of OBA payments needs to be enhanced if they are to help attract investment financing to the project. The World Bank offers guarantee instruments that can enhance the creditworthiness of such payments. There are two main options: partial risk guarantees to mitigate the risk of a government failing to make OBA payments for individual projects, and partial credit guarantees to help governments raise financing for a subsidy pool providing OBA payments to multiple project.